The competent authority to regulate the residency of a foreigner in the Iraqi and comparative law - Najem, Wattban; Mohammed, Rasha (Journal of Legal Sciences, 2022)
The authority of the state to regulate the entry and residence of foreigners to it is characterized by a great deal of freedom, and it is limited only by the rules of international law that impose on states to respect the minimum standard in the treatment of foreigners, in order to achieve the optimum protection of human rights, regardless of the society in which they live, without consideration. Regarding his nationality or his country of origin, and whatever that may be, the foreigner has now become one of those addressed by the provisions of the law of the country in which he resides, and he enjoys the rights guaranteed by his human being, without regard to his country and nationality, in other words, he has recognized his legal personality, which is not considered a mere preference. Or tolerance from the state, but it is a right that is derived from international law that guarantees to a foreigner a minimum of rights, which he enjoys vis-à-vis the state on whose land he resides.